2020
DOI: 10.3390/molecules25225287
|View full text |Cite
|
Sign up to set email alerts
|

Role of Daucus carota in Enhancing Antiulcer Profile of Pantoprazole in Experimental Animals

Abstract: The carrot plant (Daucus carota) and its components are traditionally reported for the management of gastric ulcers. This study was performed to evaluate the role of carrot when administered concurrently with a conventional antiulcer treatment, pantoprazole, in alleviating gastric and duodenal ulcers in female experimental animals. The study involved standard animal models to determine the ulcer preventive effect using pylorus ligation, ethanol, and stress induced acute gastric ulcer models and duodenal ulcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Currently, millions of people in the developing world rely on traditional medicinal plants for primary healthcare, skin care, economic benefits, and cultural development (1). Daucus carota (DC), commonly known as carrot, is a popular medicinal plant with several pharmacological activities mentioned in traditional and contemporary phytotherapy including antidiabetic (3,4), antioxidant (5,6,7), analgesic (8), a n t i m i c r o b i a l , a n t i -i n f l a m m a t o r y ( 8 ) , antihyperlipidemic (7), antifungal, diuretic, lithontripic, e m m e n a g o g u e , i n t r a o c c u l a r h y p o t e n s i v e , gastroprotective, hepatoprotective (9), aphrodistic, nephroprotective, has anti-calcifying effect in urolithiasis (10), antispasmodic, anticancer, anti-ulcer (11), adverse effect on sperm activities and sperm morphology (12), antiestrogenic (13), oestrogenic (14), cardioprotective and muscular contraction regulation effects (15), can improve antioxidant status by inhibiting peroxidation activity in liver tissue (16) and wound healing activities. No serious adverse events have been recorded after ingestion of carrot except for some cases of photosensitivity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, millions of people in the developing world rely on traditional medicinal plants for primary healthcare, skin care, economic benefits, and cultural development (1). Daucus carota (DC), commonly known as carrot, is a popular medicinal plant with several pharmacological activities mentioned in traditional and contemporary phytotherapy including antidiabetic (3,4), antioxidant (5,6,7), analgesic (8), a n t i m i c r o b i a l , a n t i -i n f l a m m a t o r y ( 8 ) , antihyperlipidemic (7), antifungal, diuretic, lithontripic, e m m e n a g o g u e , i n t r a o c c u l a r h y p o t e n s i v e , gastroprotective, hepatoprotective (9), aphrodistic, nephroprotective, has anti-calcifying effect in urolithiasis (10), antispasmodic, anticancer, anti-ulcer (11), adverse effect on sperm activities and sperm morphology (12), antiestrogenic (13), oestrogenic (14), cardioprotective and muscular contraction regulation effects (15), can improve antioxidant status by inhibiting peroxidation activity in liver tissue (16) and wound healing activities. No serious adverse events have been recorded after ingestion of carrot except for some cases of photosensitivity (13).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that it is also useful in avoiding rebleeding of ulcers, and it also has antioxidant activity by lowering calcium overload [25]. PTZ has a sulphoxide group that can scavenge hydroxyl radicals and protect cardiac cells through destruction of ROS by suppressing NADPH oxidase activity [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is critical to support reputable research into developing a muscle relaxant that is free of misuse and other undesirable consequences associated with current muscle relaxants, as well as having high efficacy in reducing muscular pain and other neuromuscular abnormalities ( Soprano et al, 2020 ). A number of recent studies have investigated the use of natural substances to treat a variety of diseases ( Asdaq et al, 2020 ). The presence of phytoconstituents in medicinal plants makes them extremely beneficial to human health.…”
Section: Introductionmentioning
confidence: 99%